Male sex workers in Iloilo City their personal history, sexual practices and behavior, and self-concept. - Casing, Dennis C. (2003.)
This descriptive study aimed to determine the socio-demographic characteristics of male sex workers in Iloilo City. It sought to describe their personal history, sexual practices and behavior, and self-concept. An in-dept unstructured interview guide was constructed by the researcher in gathering data regarding the above mentioned topics. This a study also aimed to determine the more dominant and the less dominant psychological aspects of human sexuality that are present among male sex workers. In this aspect, the Multidimensional Sexual Self-Concept Quationnaire (MSSCQ) of Dr. William E. Snell Jr. (1995) was used., Six male sex workers, whose area of operation in Iloilo City, were the respondents of this study. The results showed that their range from 19 to 30. Two of the respondents have finished their elementary education, two have finished their high school education, and the remaining two were still in high school when they stopped schooling. One of the respondents has finished one semester in college. All of them are Catholics except one, who is an Aglipay. Only one of the respondents is married, and has six children already. The family size of the respondents ranges from 6 to 14. Two of the respondents belong to broken families, while another two have already lost their fathers. Of the six respondents, only one has another job aside from that of being a male sex worker. The main reason why the respondents became male sex workers is because of poverty. Their parents do not have enough money to support their daily needs. In the mornings and afternoons, they usually loiter in malls, particularly in Marymart, The Atrium, and Robinson's Place. In the evening, they start to loiter at 9 p.m., usually in Iznart, Valeria, and Delgado streets. Customers usually arrive in taxicabs or in private automobiles. They then proceed to motels or in the houses of the customers for sexual interaction. In sex, the respondents are usually passive partners, although two admit that they perform oral sex to some of their customers in order to get bigger pay. Only one respondent admits of taking drugs, and only two have admitted to their families about their work. Although all of them do not have a clear idea regarding sexually transmitted diseases (STDs), they still use condom, particularly in anal sex. All of them wanted to stop from their work but because of lack of money, it will take some time before they will do so. Results of the MSSCQ reveal that the more dominant aspects of human sexualtiy that there present among the respondents are Sexual Problem Prevention (3.93), Motivation to avoid risky sex (3.38), Sexual Self-Schemata (3.77), Sexual Problem Management (3.60), and Sexual Monitoring (3.57). On the other hand, the less dominant sexual aspects of human sexuality that are present among the respondents are Fear of Sex (1.43), Sexual Preoccupation (1.57), Chance/Luck Sexual Control (1.90), Sexual Assertiveness (1.93), and Sexual Depression (1.97).
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP in the Visayas, Miagao, Iloilo
Keywords: Sex Workers -- Male